Substrate Specificities of MexAB-OprM, MexCD-OprJ, and MexXY-OprM Efflux Pumps in Pseudomonas aeruginosa - Masuda, Nobuhisa (American Society for Microbiology, 2000)
To find the exact substrate specificities of three species of tripartite efflux systems of Pseudomonas aeruginosa, MexAB-OprM, MexCD-OprJ, and MexXY-OprM, we constructed a series of isogenic mutants, each of which constitutively overproduced one of the three efflux systems and lacked the other two, and their isogenic mutants, which lacked all these systems. Comparison of the susceptibilities of the constructed mutants to 52 antimicrobial agents belonging to various groups suggested the following substrate specificities. All of the efflux systems extrude a wide variety of antimicrobial agent groups, i.e., quinolones, macrolides, tetracyclines, lincomycin, chloramphenicol, most penicillins (all but carbenicillin and sulbenicillin), most cephems (all but cefsulodin and ceftazidime), meropenem, and S-4661, but none of them extrude polymyxin B or imipenem. Extrusion of aminoglycosides is specific to MexXY-OprM, and extrusion of a group of the β-lactams, i.e., carbenicillin, sulbenicillin, ceftazidime, moxalactam, and aztreonam, is specific to MexAB-OprM. Moreover, MexAB-OprM and MexCD-OprJ extrude novobiocin, cefsulodin, and flomoxef, while MexXY-OprM does not. These substrate specificities are distinct from those reported previously.